Bargaining with criminals: The morality of witness collaboration in Mexico's “war on drugs” - Espíndola Mata, Juan (Theoretical criminology, 2023)
Public authorities take considerable and oftentimes controversial steps in their efforts to dismantle criminal organizations involved in drug trafficking and related crimes in Mexico. Among other things, they recruit offenders who abandon their criminal organization and strike a deal with law enforcement agents and prosecutors to share information about their co-perpetrators in exchange for leniency in sentencing as well as of protection from retaliation. This article explores whether the deployment of collaborators is morally permissible in view of the significant risks it exposes them to, most notably retaliatory aggressions. The article examines the underlying philosophical problem regarding the justifiability of deploying collaborators in the social and political circumstances prevailing in the country. The normative framework I advance to explore the Mexican case can be useful in examining the ethical implications of using collaborating witnesses elsewhere.